2018
DOI: 10.1364/boe.9.006400
|View full text |Cite
|
Sign up to set email alerts
|

Integrated RFA/PSOCT catheter for real-time guidance of cardiac radio-frequency ablation

Abstract: Radiofrequency ablation (RFA) is an important standard therapy for cardiac arrhythmias, but direct monitoring of tissue treatment is currently lacking. We demonstrate an RFA catheter integrated with polarization sensitive optical coherence tomography (PSOCT) for directly monitoring the RFA process in real time. The integrated RFA/OCT catheter was modified from a standard clinical RFA catheter and includes a miniature forward-viewing cone-scanning OCT probe. The PSOCT system was validated with a quarter-wave pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 36 publications
(37 reference statements)
0
35
0
Order By: Relevance
“…Several studies have demonstrated the development of OCT‐integrated catheters that may be useful for ablation guidance, in vivo. With OCT's video‐rate imaging speeds and high resolution, these studies have focused on the application of using OCT‐integrated catheters to monitor ablation lesion formation in real‐time . In addition to imaging lesions, OCT‐integrated catheters could simultaneously provide a real‐time, high‐resolution characterization of the left atrial tissue structure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have demonstrated the development of OCT‐integrated catheters that may be useful for ablation guidance, in vivo. With OCT's video‐rate imaging speeds and high resolution, these studies have focused on the application of using OCT‐integrated catheters to monitor ablation lesion formation in real‐time . In addition to imaging lesions, OCT‐integrated catheters could simultaneously provide a real‐time, high‐resolution characterization of the left atrial tissue structure.…”
Section: Discussionmentioning
confidence: 99%
“…16 these studies have focused on the application of using OCTintegrated catheters to monitor ablation lesion formation in realtime. [3][4][5][6]18,19 In addition to imaging lesions, OCT-integrated catheters could simultaneously provide a real-time, high-resolution characterization of the left atrial tissue structure. However, there exists a lack of OCT data over the human left atrium to inform this application.…”
Section: Fiber Orientation Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Comprehensive OCT imaging of the human pulmonary veins has visualized collagen fibers in the venous myocardial sleeves, including varying organization among different veins . Finally, OCT‐integrated catheters have been developed for the monitoring of lesion formation during ablation procedures for atrial fibrillation, with some demonstrations in vivo . Therefore, OCT may be able to offer real‐time visualization during catheter‐based therapies.…”
Section: Introductionmentioning
confidence: 99%